Learning Methods Of Keroncong Music Extracurricular On Junior High School (SMP) In Purbalingga (Jurnal Seni Musik, 2022)
SMP Negeri 1 Karangmoncol in Purbalingga Regency is the only junior high school in Purbalingga that implements keroncong extracurricular activities. The purpose of implementing the keroncong extracurricular is introduce keroncong music to students. The problem in this research is how the keroncong music extracurricular learning method in SMP Negeri 1 Karangmoncol. The research method used is descriptive qualitative. Data were obtained through interviews, qualitative observation, and documentation. The results show that (1) there are five methods used by the keroncong extracurricular teacher in the keroncong extracurricular learning process, five of which were the lecture method, the discussion method, the question and answer method, the peer tutoring method, and the drill method; (2) From the five methods, it is found that the drill method is the most frequently used in the learning process. It is because the keroncong extracurricular requires more psychomotor skills from students to be more skilled and fluent in playing keroncong musical instruments.